Daily life activities in patients with Alzheimer's disease or semantic dementia: Multitasking assessment. (8th January 2021) - Jarry, Christophe; Osiurak, François; Baumard, Josselin; Lesourd, Mathieu; Coiffard, Clémence; Lucas, Charlène; Merck, Catherine; Etcharry-Bouyx, Frédérique; Chauviré, Valérie; Belliard, Serge; Moreaud, Olivier; Croisile, Bernard; et al.
Abstract: The aim of the present study was to compare patients with mild to moderate Alzheimer's disease (AD) or semantic dementia (SD) on their cognitive processes and the severity of their daily life activity impairments. Three types of tasks were administered to patients (SD = 15; AD = 31) and 30 healthy controls (HC): 1) informant-based scales and questionnaires, 2) a neuropsychological assessment exploring executive functions, episodic and semantic memory, and 3) a new original test featuring multi-step naturalistic actions and multitasking: the Sequential Daily Life Multitasking (SDLM). We predicted that patients with AD would mainly exhibit task perplexity, associated with episodic and executive deficits on the SDLM, while the behavior of patients with SD would mostly be characterized by object perplexity, associated with semantic memory deficits. Results showed that patients with AD or SD were impaired across all neuropsychological tests, particularly episodic memory in AD and semantic memory in SD. General performance on the SDLM also appeared dramatically impaired in both patient groups, and correlated with results of questionnaires about instrumental activities and memory impairments. However, specific qualitative measurements on the SDLM did not allow us to pinpoint different patterns of errors and behavior in patients with AD versus SD. We suggest that the inability of patients in both groups to perform the SDLM may derive from a constellation of disorders or else from more subtle impairment of cognitive and conative processes that requires further exploration. Highlights: Multitasking impairment occurs early in Alzheimer's disease and semantic dementia. New tasks and measurements are needed to explore everyday action impairment. Patients with these diseases show perplexity, exploring objects but not using them. These patients exhibit varying sensitivity to distractor items and task conditions. .